Odpowiedź:
Szczegółowe wyjaśnienie:
a) 3(x²-2x+3)-2(x²-5x-1) dla x=2
Upraszczamy wyrażenie:
3(x²-2x+3)-2(x²-5x-1) = 3x²-6x+9-2x²+10x+2 = x²+4x+11
Teraz wstawiamy x = 2 do powyższego "wyniku":
x²+4x+11 = 2²+(4 razy 2)+11 = 4+8+11 = 23
b) a(2ab + b) – b(a - 2ab + a²) dla a=0,1 i b = -10
Upraszczamy wyrażenie:
a(2ab + b) – b(a - 2ab + a²) = 2a²b + ab - ab + 2ab² - a²b = a²b + 2ab²
= ab (a+2b)
Wstawiamy a = 0,1 i b = -10:
ab (a+2b) = (0,1 razy (-10)) razy (0,1 + 2 razy (-10)) = -1 razy (0,1-20) =
-1 razy (-19,9) = 19,9